Photoresponsive prodrugs of butyric acid based on amino naphthopyranones - Soares, Ana M. S. (2012)
In order to evaluate the application of new 7-amino-naphtho[1,2-b]pyran-2-ones as photoactive groups in the preparation of carboxylic acid derivatives, model butyric ester conjugates were synthesised by reaction with the chloromethylated heterocyclic precursor. Photocleavage studies of the ester conjugates in methanol/HEPES buffer (80:20) solution at different wavelengths of irradiation (254, 300, 350 and 419 nm) confirmed the quantitative release of the model acid in short irradiation times.